Digitale communicatie over existentiële vragen en spiritualiteit in het kader van persoonsgerichte zorg in het ziekenhuis: Een toekomstgericht perspectief - Grevel, Sylvia (Religie & Samenleving, 2020)
This article is about digital communication on existential and spiritual matters within person-centered care in hospitals. The explorative qualitative research aimed to get a deeper insight into the ways health care professionals (including spiritual care providers), can establish and then keep contact with patients when it is harder to have face-to-face conversations. In interviews and focus groups with stakeholders and experts, I have tried to find answers to the following research question: “Are there existing instruments in digital communication available, or is there a need to develop new tools, to use for personal communication on existential and spiritual matters when there is no possibility for face-to-face conversations?” The results of the research are diverse but consistent. Most of the respondents are opting for the use of the existing digital communication tools like Skype, WhatsApp etc. No particular mode was favoured. However, although digital communication is considered to be a good aid, face-to-face contact was nevertheless much more appreciated over digital means of communication. As a spin off there are ideas about possibilities to develop new ways of digital communication on the meaning of life and spirituality. In the article I also reflect on the impact of Covid-19 from a personal experience as a recent immigrant. We are living in extremely turbulent times. Ongoing turbulence might be the new normal. This all leads to a new question for future-proof spiritual care: “Can digital communication successfully replace traditional faceto- face communication in the realms of spiritual care? Or is also retaining more traditional face-to-face communication vitally important?”